Green synthesis of iron nanoparticles to promote seed germination of Zea mays under salinity condition - Hiba Fouad Abdulfatah; May Fahmi Abdulrahman; Enas Fahd Naji (Heliyon)
The application of green synthesis of nanoparticles in agriculture serves as an environmentally benign strategy. Pomegranate Peel extract (PPE) was utilized to produce iron nanoparticles (Fe NPs). PPE contains biomaterials that have the ability to synthesize Fe NPs through the reduction the iron precursor salt (FeSO4•7H2O) and also act as capping and stabilizing agents. UV–Visible, FTIR, XRD, SEM, EDX, and nano zeta-potential analysis were used to investigate Fe NPs. The synthesis of Fe NPs was confirmed by a significant color change from yellow to black. Then Fe NP production is confirmed by a UV–Visible peak at 301 nm. FTIR showed O–H and C=C stretching due to phenol and alkene functional groups. X-ray diffraction showed that Fe NPs are mostly amorphous. The synthesized Fe NPs were spherical and have around 12 nm in size, with a 5.5 mV value, the synthesized Fe NPs were stable.The effects of these (Fe NPs) on the germination of maize (Zea mays L.) labeled Z1(Buhooth 5018), Z2(Baghdad-3) and Z3 (Fajr-1) seeds and the growth of their roots were assessed under conditions of salinity at different levels (0, 8, 12 ds m−1) in a laboratory-scale system. The findings indicated that the application of the synthesized Fe NPs at a concentration of 20 Mm caused an increase in germination ratio, root and shoot length, seedling vigor index, root length stress tolerance index (RLSTI) and shoot length stress tolerance index (SLSTI). The findings showed that the stress-relieving benefits of Fe NPs were more effective than normal forms, which may be related to their distribution, shape, size, and other properties. In general, the results of the present research indicate that utilizing pomegranate peel extract for eco-friendly production of nanoparticles could enhance the germination of seeds and the strength of seedlings in Zea mays.